Evaluate the utility of Iraqi Ephedra Transitoria methyl extract on the proliferation of cervical cancer cell line: Utility of Iraqi Ephedra Extract on Cervical Cancer Cells - Azal Hamoody Juma; Mahdi, Montadher; Abdulla, Kawakeb; Dawood, Yasser (Iraqi Journal of Cancer and Medical Genetics, 2024)
Objective: This study aimed to assess the inhibitory effect of a methanolic extract of Iraqi Ephedra transitoria on the proliferation of cervical cancer cells. Materials and methods: To assess the anticancer properties of Ephedra transitoria, a HeLa cell line (derived from cervical cancer) was utilized. The concentration of the evaluated agent was varied between 0.1 and 1000 µg/ml, and the cells were incubated for 24 and 72 hours. The IC50 value was used to identify the potency of the examined substance. Results: The study results demonstrated that the extraction ratio of E. transitoria was 8%. Additionally, a cytotoxicity study revealed that the plant extract can potentially inhibit the proliferation of human cervical cancer cells in a concentration- and time-dependent manner. The extract at a concentration of 1000 µg/ml inhibited growth by 88% after 72 hours. The comparison between the cytotoxicity of a plant extract and traditional anticancer chemotherapy (cisplatin) revealed that the plant extract exhibited higher cytotoxicity than cisplatin in the HeLa cancer cell line after two incubation periods. Additionally, the IC50 value of the extract was lower than that of cisplatin. Conclusion: Ephedra transitoria inhibits the proliferation of cervical cancer cells via cell cycle-specific and cell cycle-nonspecific mechanisms, thus demonstrating its anticancer properties. The study also revealed that, compared with cisplatin, the plant extract exhibited superior efficacy and potency in cancer treatment.